Memory and voice of the illiterate women. Other lineages in Argentine literature (Anclajes, 2025)
The memory of illiterate women has a discontinuous presence in Argentine literature, although persistent throughout history. In recent years, gender studies, sexual dissidence and feminism have made more visible a popular or plebeian literary lineage in which authors such as María Moreno, Camila Sosa Villada or Gabriela Cabezón Cámara belong. We investigate her autobiographical writings, chronicles, autofictions and fictions, texts in which the configuration of what I called here women without letters or without a book appears. It is about analyzing the intimate, extimate and public inflections of those plebeian voices that permeate literate culture, imprinting their legacy on contemporary literature.
Keywords: Camila Sosa Villada; María Moreno; Gabriela Cabezón Cámara; Annie Ernaux; Illiteracy